Exploration of multi‐target effects of 3‐benzoyl‐5‐hydroxychromen‐2‐one in Alzheimer’s disease cell and mouse models - Lin, Te‐Hsien (Aging Cell, 2020)
Microtubule‐associated protein Tau, abundant in the central nervous system (CNS), plays crucial roles in microtubule assembly and stabilization. Abnormal Tau phosphorylation and aggregation are a common pathogenic hallmark in Alzheimer's disease (AD). Hyperphosphorylation of Tau could change its conformation and result in self‐aggregation, increased oxidative stress, and neuronal death. In this study, we examined the potential of licochalcone A (a natural chalcone) and five synthetic derivatives (LM compounds) for inhibiting Tau misfolding, scavenging reactive oxygen species (ROS) and providing neuroprotection in human cells expressing proaggregant ΔK280 Tau(RD)‐DsRed. All test compounds were soluble up to 100 μM in cell culture media and predicted to be orally bioavailable and CNS‐active. Among them, licochalcone A and LM‐031 markedly reduced Tau misfolding and associated ROS, promoted neurite outgrowth, and inhibited caspase 3 activity in ΔK280 Tau(RD)‐DsRed 293 and SH‐SY5Y cells. Mechanistic studies showed that LM‐031 upregulates HSPB1 chaperone, NRF2/NQO1/GCLC pathway, and CREB‐dependent BDNF/AKT/ERK/BCL2 pathway in ΔK280 Tau(RD)‐DsRed SH‐SY5Y cells. Decreased neurite outgrowth upon induction of ΔK280 Tau(RD)‐DsRed was rescued by LM‐031, which was counteracted by knockdown of NRF2 or CREB. LM‐031 further rescued the downregulated NRF2 and pCREB, reduced Aβ and Tau levels in hippocampus and cortex, and ameliorated cognitive deficits in streptozocin‐induced hyperglycemic 3 × Tg‐AD mice. Our findings strongly indicate the potential of LM‐031 for modifying AD progression by targeting HSPB1 to reduce Tau misfolding and activating NRF2 and CREB pathways to suppress apoptosis and promote neuron survival, thereby offering a new drug development avenue for AD treatment.